Resilience in maternal and child nutrition outcomes in a refugee-hosting community in Cameroon: A quasi-experimental study - Tatah, Lambed; Nkunzimana, Tharcisse; Foley, Louise; de Brauw, Alan; Rodriguez-Llanes, Jose Manuel (Elsevier, 2022)
Refugees may be perceived as a burden to their host communities, and nutrition insecurity is a critical area of contention. We explored the relationship between refugee presence and a host community’s resilience in nutrition outcomes in Cameroon. We also tested an analytical framework for evaluating community resilience during shocks. We used data from repeated cross-sectional Demographic and Health Surveys in Cameroon (2004 and 2011), data on refugee movement, and data on extreme climatic events, epidemics, and conflicts from multiple sources. Outcome variables were maternal underweight, maternal anaemia, and child underweight, anaemia, stunting and wasting. The exposure variable was residence within an area in which refugees settled. We used a genetic matching algorithm to select controls from the rest of the country after excluding areas experiencing concurrent shocks. We used a difference-in-differences analysis to compare outcomes between the exposed and control areas. The 2004 survey comprised 10,656 women and 8,125 children, while the 2011 survey comprised 15,426 women and 11,732 children. Apart from anaemia which showed a decreasing trend in both the refugee-hosting community and the rest of the country, all other indicators (wasting, underweight and stunting) showed increasing trends in the refugee-hosting community but decreasing trends in the rest of the country. The matched control group showed a similar trend of decreasing trend for all the indicators. Controlled comparisons showed no evidence of an association between changes in nutrition outcomes and the presence of refugees. These findings contest a common perception that refugees negatively impact hosting communities. The difference-in-differences analysis and an improved matching technique offer a method for exploring the resilience of communities to shocks.